Upaya Penanganan Perilaku Agresif pada Remaja Pelaku Klitih - Rachmayanti, Januarni Dwi; Nuryanti, Lusi (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2024)
This study analyzes efforts to deal with aggressive behavior of klitih perpetrators in the Special Region of Yogyakarta (DIY) using Bronfenbrenner's Ecological Theory. Through a qualitative literature review of 30 articles (2010-2022), this study reveals that klitih is influenced by complex interactions between ecological systems. Key factors include family dynamics, peer influence, lack of school-family coordination, and normalization of violence in society. While existing interventions have shown positive results, a more holistic approach is needed. It was concluded that effective strategies must be multidimensional, involve multiple stakeholders and integrate interventions at all levels of the system. Recommendations include family strengthening programs, peer support, school-family collaboration, and public campaigns to change perceptions of youth violence.